Analysis of Indonesia's Loss against the United States of America in the Horticultural Trade Dispute at the World Trade Organization - Miryanti, Renny; Baniyah, Siti (KnE Social Sciences, 2023)
This paper examined the World Trade Organization (WTO) trade dispute settlement between Indonesia and the United States of America on the horticultural issue in 2018 . The WTO aims to encourage free trade mechanisms by eliminating trade barriers, providing a negotiation forum for international trade disputes, and as a mediator to international negotiation forums on trade dispute settlement. The USA reported Indonesia to the Dispute Settlement Body (DSB) of the WTO because Indonesia was considered to have implemented a number of policies on imports of agricultural products that created trade barriers to the USA’s products. This research will explain the causes of Indonesia’s loss in the dispute by using Susan Strange’s concept of structural power. This research used qualitative methods and obtained data sources through primary and secondary data sources. Primary data was obtained directly through field study by interviewing related parties in the Ministry of Agriculture and the Ministry of Trade of The Republic of Indonesia. Secondary data was collected by conducting literature reviews of journals, books, news, and other sources. It showed that Indonesia was defeated in the dispute because it violated the quantitative restrictions rules in article XI. I GATT 1994. The USA used its knowledge structural power, such as the existence of scientific studies and research, to strengthen its case. Indonesia could not match the knowledge structure that the USA had. This was seen in Indonesia’s weaknesses in a legal capacity and inability to show facts based on research and scientific studies regarding Indonesia’s actions. Keywords: Defeat, Dispute Settlement Body WTO, Horticultural, Indonesia, United States of America